Determination of occurrence of escherichia coli ATCC 25922 antibiotic resistance mutants as a result of exposure to subinhibitory concentration of β-lactam antibiotic, ampicillin - Latha S Davandran (2024)
This study explores the emergence of antibiotic resistance mutants in Escherichia coli ATCC 25922 resulting from exposure to subinhibitory concentrations of the beta-lactam antibiotic ampicillin. Escherichia coli ATCC 25922 was exposed to various concentrations of ampicillin, revealing concentration-dependent effects on bacterial growth. Subinhibitory concentrations demonstrated a hormesis effect, enhancing growth during the exponential phase. Sub-MIC ampicillin induced mutagenesis, implying the potential for adaptive responses under environmental stress. Cultures exposed to 5 μg/mL ampicillin exhibited a concentration-dependent response, indicating the emergence of resistant strains. Conversely, higher concentrations exerted inhibitory effects. The investigation underscored the intricate balance between inhibitory and subinhibitory concentrations, emphasizing the necessity for refined dosing strategies in antibiotic administration. This study provides valuable insights into the dynamic interactions between antibiotics and bacterial populations, offering perspectives on the implications for effective dosing strategies in combating antibiotic resistance